Odpowiedzi

2009-12-09T19:03:50+01:00
3(√13+2√13)-3√13= 3√13 + 6√13 - 3√13= 6√13
2(√2-5√5)-5√2+2√5= 2√2 - 4√5 - 5√2 +2√5= -3√2 - 2√5
5(5√2+2)-2(2√2+2)= 25√2 +10 -4√2 - 4= 21√2 +6
1 5 1
Najlepsza Odpowiedź!
2009-12-09T19:06:46+01:00
3(√13+2√13)-3√13=(3 √13 + 6√13 ) - 3√13= 9√13 - 3√13 = 6√13

2(√2-5√5)-5√2+2√5=2√2 - 10√5 - 5√2 + 2√5 = -3√2 - 8√5

5(5√2+2)-2(2√2+2)= 25√2 + 10 - 4√2 - 4 = 21√2 + 6
1 5 1
2009-12-09T19:11:48+01:00
3(√13+2√13)-3√13=3×3√13-3√13=9√13-3√13=6√13
2(√2-5√5)-5√2+2√5=2√2-10√5-5√2+2√5=-3√2-8√5
5(5√2+2)-2(2√2+2)=25√2+10-4√2-4=21√2+6
1 5 1